94.7k views
2 votes
8 - (7/10)t = 6 - (1/5)t

User Caroleann
by
4.6k points

1 Answer

4 votes

Answer:

t = 4

Explanation:

Solve for t:

8 - (7 t)/10 = 6 - t/5

Hint: | Put the fractions in 8 - (7 t)/10 over a common denominator.

Put each term in 8 - (7 t)/10 over the common denominator 10: 8 - (7 t)/10 = 80/10 - (7 t)/10:

80/10 - (7 t)/10 = 6 - t/5

Hint: | Combine 80/10 - (7 t)/10 into a single fraction.

80/10 - (7 t)/10 = (80 - 7 t)/10:

1/10 (80 - 7 t) = 6 - t/5

Hint: | Put the fractions in 6 - t/5 over a common denominator.

Put each term in 6 - t/5 over the common denominator 5: 6 - t/5 = 30/5 - t/5:

(80 - 7 t)/10 = 30/5 - t/5

Hint: | Combine 30/5 - t/5 into a single fraction.

30/5 - t/5 = (30 - t)/5:

(80 - 7 t)/10 = (30 - t)/5

Hint: | Make (80 - 7 t)/10 = (30 - t)/5 simpler by multiplying both sides by a constant.

Multiply both sides by 10:

(10 (80 - 7 t))/10 = (10 (30 - t))/5

Hint: | Cancel common terms in the numerator and denominator of (10 (80 - 7 t))/10.

(10 (80 - 7 t))/10 = 10/10×(80 - 7 t) = 80 - 7 t:

80 - 7 t = (10 (30 - t))/5

Hint: | In (10 (30 - t))/5, divide 10 in the numerator by 5 in the denominator.

10/5 = (5×2)/5 = 2:

80 - 7 t = 2 (30 - t)

Hint: | Write the linear polynomial on the left hand side in standard form.

Expand out terms of the right hand side:

80 - 7 t = 60 - 2 t

Hint: | Move terms with t to the left hand side.

Add 2 t to both sides:

2 t - 7 t + 80 = (2 t - 2 t) + 60

Hint: | Look for the difference of two identical terms.

2 t - 2 t = 0:

2 t - 7 t + 80 = 60

Hint: | Group like terms in 2 t - 7 t + 80.

Grouping like terms, 2 t - 7 t + 80 = 80 + (2 t - 7 t):

80 + (2 t - 7 t) = 60

Hint: | Combine like terms in 2 t - 7 t.

2 t - 7 t = -5 t:

-5 t + 80 = 60

Hint: | Isolate terms with t to the left hand side.

Subtract 80 from both sides:

(80 - 80) - 5 t = 60 - 80

Hint: | Look for the difference of two identical terms.

80 - 80 = 0:

-5 t = 60 - 80

Hint: | Evaluate 60 - 80.

60 - 80 = -20:

-5 t = -20

Hint: | Divide both sides by a constant to simplify the equation.

Divide both sides of -5 t = -20 by -5:

(-5 t)/(-5) = (-20)/(-5)

Hint: | Any nonzero number divided by itself is one.

(-5)/(-5) = 1:

t = (-20)/(-5)

Hint: | Reduce (-20)/(-5) to lowest terms. Start by finding the GCD of -20 and -5.

The gcd of -20 and -5 is -5, so (-20)/(-5) = (-5×4)/(-5×1) = (-5)/(-5)×4 = 4:

Answer: t = 4

User Tsivia
by
5.0k points